Parental awareness about the presence of permanent first molars and its relation to DMFT index in 7-9-year-old children - Javane Vejdani; Narjes Amrollahi; Maryam Amrollahi; Zahra Peirowfeiz; Donya Alinejad (Islamic Dental Association of Iran, 2018)
Background and Aim: Permanent first molars (PFMs) are highly susceptible to caries due to their special anatomical form, early eruption, lack of awareness about their eruption and misidentifying them from the primary teeth. Parental awareness about the existence of PFMs in their children's mouth could lead to caries prevention. This study aimed to determine the level of parental awareness about the presence of PFMs and its relation to DMFT index in 7-9-year-old children in Rasht. Materials and Methods: This analytical cross-sectional study was conducted on 553 elementary school students in Rasht. Cluster random sampling was done. A checklist was filled out by the parents after obtaining their informed consent. Intraoral examination was performed by one specialist using a dental mirror, an explorer and a head light. Children's DMFT index of PFMs (DMFT6) was recorded. Data were entered into SPSS software version 21. Chi- square test, Cochran's test, sign test and logistic regression model were used for statistical analysis. Results: In this study, only 151 parents (27.3%) knew about the PFMs' eruption time. DMFT6 was 0.48±0.84 in 7-9-year-olds. There was a significant correlation between DMFT6 and the frequency of consumption of sugary snacks (P=0.025) and toothbrushing (P=0.016). But the correlation between DMFT6 and parental knowledge (P=0.918), gender (P=0.44), father's educational level (P=0.103) and mother's educational level (P=0.145) was not significant. Conclusion: Considering the low level of awareness of parents, attention to early education, prevention and treatment is necessary.